Beta-Carotene, Vitamin E, MDA, Glutathione Reductase and Arylesterase Activity Levels in Patients with Active Rheumatoid Arthritis - N Aryaeian; M Djalali; F Shahram; Sh Jazayeri; M Chamari; SA Nazari (Tehran University of Medical Sciences, 2011)
"nBackground: Many studies have investigated the possible role of reactive oxygen species in the etiology and pathogenesis of Rheumatoid Arthritis (RA). The aim of this study was to investigate the activities of some antioxidants in RA patients."nMethods: In this case-control study, 59 RA patients and 60 healthy sex and age-matched controls were selected. Vitamin E and Beta-carotene were determined using HPLC. Erythrocytes glutathione reductase (GR) activity was measured spectrophotometrically, and malondialdehyde (MDA) was determined by colorimetric method. Arylesterase activity (AEA) was measured by Phenylacetate. The clinical data were determined by a rheumatologist, medical history and filling the questionnaire by interview. Statistical analyses were carried out using the SPSS software."nResults: In patients with RA, serum MDA level was significantly higher and plasma concentration of vitamin E, Beta-carotene and GR activity, were significantly lower than healthy control (P<0.001). AEA activity differences between two groups were non-significant."nConclusions: Oxidative stress may play an important role in the inflammation and pathogenesis of RA.